Temperature simulation and its application in on-line temperature measurement of a micro drill bit. Issue 1 (2nd February 2015) - Shi, Hongyan; Li, Hui; Chen, Shengzhi
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to obtain the micro drill bit temperature field distribution in micro-drilling process and the temperature drop in retracting process with simulation software. Meanwhile, the key factors that affect the micro drill bit temperature will be obtained as well. The results can also be used to improve the accuracy in on-line drilling temperature measurement. Design/methodology/approach – The purpose of this paper is to obtain the micro drill bit temperature field distribution in micro-drilling process and the temperature drop in retracting process with simulation software. Meanwhile, the key factors that affect the micro drill bit temperature will be obtained as well. The results can also be used to improve the accuracy in on-line drilling temperature measurement. Findings – Micro drill bit high-temperature area mainly concentrates in the cutting edge and chisel edge. With the increase of spindle speed and feed speed, the micro drill bit highest temperature increased. The micro drill bit temperature drop rate reaches 20° in the micro-drilling retraction process with certain parameters. The micro drill bit highest temperature detected by an infrared camera is lower by 22° than that in real drilling. The simulation results can be used to guide the actual industrial production. Originality/value – The simulation results can be applied to revise the temperature measurement by an infrared camera in the drilling process. Drilling experiments show that the simulation method is correct and has certain practical significance. The current temperature measurement method can satisfy most of the requirements of temperature measurements.